2017
DOI: 10.3390/informatics4020009
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Providing an International Virtual Elective Experience for Student Nurses

Abstract: The advances in social media offer many opportunities for developing understanding of different countries and cultures without any implications of travel. Nursing has a global presence and yet it appears as though students have little knowledge of the health and social care needs and provision outside their local environment. Our collaboration across three countries, New Zealand, United Kingdom, and the United States of America, brought the two themes together with the aim of senior student nurses having a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Even in the absence of international travel, experiences can be created that allow students to learn about and reflect on cultures other than their own (Phillips & Young, 2018). Procter et al (2017) found that social media platforms assisted in developing an understanding of another country’s culture without leaving home. Todhunter et al (2013) expressed that a virtual “study-elsewhere” experience supported nursing students’ understanding of health care around the world.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the absence of international travel, experiences can be created that allow students to learn about and reflect on cultures other than their own (Phillips & Young, 2018). Procter et al (2017) found that social media platforms assisted in developing an understanding of another country’s culture without leaving home. Todhunter et al (2013) expressed that a virtual “study-elsewhere” experience supported nursing students’ understanding of health care around the world.…”
Section: Discussionmentioning
confidence: 99%